Effect of fluorine substitution on the crystal structures and vibrational properties of phenylthiourea isomers - Saeed, Aamer (2010)
The 1-(2-chlorobenzoyl)-3-(isomeric fluorophenyl)thiourea derivatives (1–3) were prepared by the reaction of 2-chlorobenzoyl isothiocyanate produced in situ with isomeric fluoroanilines in excellent yields. The novel compounds are characterized by multinuclear (1 H and 13C) NMR, GC–MS, elemental analyses and FTIR spectroscopy techniques. Structural and conformational properties of compounds 1–3 are analyzed using a combined approach including X-ray diffraction, vibrational spectra (solid FTIR and FTRaman) and theoretical calculation methods. The crystal structures have been determined by X-ray diffraction methods. The three species crystallize in the monoclinic C2/c space group with and Z = 8 molecules per unit cell. The carbonyl and thiourea groups are almost planar and the conformation adopted by the C@S and the C@O double bonds is antiperiplanar. The crystal lattices show the presence of centrosymmetric dimeric units held by NHS hydrogen bonds stacked along the [0 1 0] plane. The effect of fluorine substitution on the vibrational properties and on the conformational space has been determined by quantum chemical calculations (B3LYP functional in connection with the 6-311+G basis sets) and vibrational spectroscopy.